Not-that-heavy Majorana neutrino signals at the LHC - Duarte, Deborah Lucia (2017)
We revisit the possibility of Majorana neutrinos production at the Large Hadron Collider (LHC)by studying the pp → l i + l j + + 2 jets (l j ≡ e, μ) process which, due to leptonic number violation,is a clear signature for intermediate Majorana neutrino contributions. The interactions betweenMajorana neutrinos and the Standard Model particles are obtained from an effective Lagrangianapproach. Majorana neutrinos with masses of a few GeV are long-lived neutral particles, and wetake advantage of its measurable decay length: in the same-sign dilepton channel, we exploit thisfact imposing cuts that reject the SM background, and analyze the distribution corresponding tothe angle between the final leptons, using a forward-backward like asymmetry to study the effectsof the different gauge invariant operators. We also study the pp → l i + νγ process, which is dominantfor low m N masses if tensorial one-loop generated new physics leading to a magnetic moment forthe heavy neutrinos is present. This channel provides a powerful signal that could be observed atthe LHC with the aid of non-pointing photons observables and cuts on the displacement betweenthe prompt lepton and the photon in the final state.